A comparative study of participles, converbs and absolute constructions in Hindi and Medieval Rajasthani - Tokaj, Joanna (Lingua Posnaniensis, 2016)
The PRO coindexation of converbs and participles in South Asian Languages along with Subject Identity Constraint (Subject Control) violation has been studied by Subbarao (2012) and Murthy (1994). I present the analysis of Medieval Rajasthani data focusing on two construction types - constructions consisting of converbs and participles. I compare my findings on Rajasthani with previous analyses of the Hindi language. I demonstrate that PRO coindexation in Medieval Rajasthani is more strict than in Hindi. Participles are coindexed with a subject or a direct object of the main clause while converbs are most often subject-oriented. Subject Identity Constraint (Subject Control) violation in Medieval Rajasthani (MR) occurs in constructions consisting of participles and converbs. Subject Identity Constraint may be violated in MR in sentences denoting cause and effect and time relation.